HBV-associated DLBCL of poor prognosis: advance in pathogenesis, immunity and therapy - Wan, Xin; Young, Ken H.; Bai, Ou (Frontiers in Immunology, 2023)
Advanced studies have shown a biological correlation between hepatitis B virus (HBV) and B-cell lymphoma, especially diffuse large B-cell lymphoma (DLBCL). Patients with DLBCL infected with HBV (HBV-associated DLBCL) are clinically characterized by an advanced clinical stage, poor response to front-line immunochemotherapy regimens, and worse clinical prognosis. HBV-associated DLBCL often exhibits abnormal activation of the nuclear factor kappa B pathway as well as mutations in oncogenes, including Myc and BCL-6. Currently, there is no consensus on any specific and effective treatment for HBV-associated DLBCL. Therefore, in this review, we comprehensively and mechanistically analyzed the natural history of HBV infection and immunity, including HBVmediated oncogenes, immune escape, epigenetic alterations, dysregulated signaling pathways, and potential therapeutic approaches for HBV-associated DLBCL. We hope that an improved understanding of the biology of HBV-associated DLBCL would lead to the development of novel therapeutic approaches, enhance the number of effective clinical trials, and improve the prognosis of this disease.